Privacy concerns, voluntary disclosure of information, and unraveling: An experiment - Volker Benndorf; Dorothea Kübler; Hans-Theo Normann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We study the voluntary revelation of private, personal information in a labor-market experiment with a lemons structure where workers can reveal their productivity at a cost. While rational revelation improves a worker's payout, it imposes a negative externality on others and may trigger further unraveling. Our data suggest that subjects reveal their productivity less frequently than predicted in equilibrium. A loaded frame emphasizing personal information about workers' health leads to even less revelation. We show that three canonical behavioral models all predict too little rather than too much revelation: level-k reasoning, quantal-response equilibrium, and to a lesser extent inequality aversion.
Keywords: C72; C90; C91; 330; information revelation; privacy; lemons market; level-k reasoning; quantalresponse equilibrium; inequality aversion